Dependence of Adhesion Property of Epoxidized Natural Rubber (ENR 25)/Ethylene-Propylene-Diene Rubber Blend Adhesives Crosslinked by Benzoyl Peroxide - Poh, B. T.; Teh, Y. Y. (Hindawi Publishing Corporation, 2014)
The loop tack, peel strength, and shear strength of crosslinked epoxidized natural rubber (ENR 25)/ethylene-propylene-diene rubber (EPDM) blend adhesives were investigated. Coumarone-indene resin, toluene, and benzoyl peroxide were used as the tackifier, solvent, and crosslinking agent, respectively, throughout the experiment. The adhesive was coated on a polyethylene terephthalate (PET) substrate using a SHEEN hand coater at 60